2006
DOI: 10.1111/j.1469-0691.2006.01519.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among genotypes, virulence and clinical forms of Sporothrix schenckii infection

Abstract: This study explored the relationships among genotypes, virulence and clinical forms of Sporothrix schenckii. Genomic DNA from isolates of S. schenckii, collected from different clinical forms of sporotrichosis, was amplified by randomly amplified polymorphic DNA (RAPD). Suspensions of different isolates of S. schenckii were inoculated into healthy BALB/c mice to compare their virulence, and the numbers and distribution of spores were determined by histological analysis. RAPD analysis indicated that the isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 21 publications
2
19
0
5
Order By: Relevance
“…35 Some comparative studies were conducted correlating the route of experimental infection 32 or clinical manifestation in humans with the virulence degree of different isolates. 33,34 Recently, Arrillaga-Moncrieff et al 2,3 showed different degrees of virulence among S. schenckii s. str., S. brasiliensis and S. globosa species.…”
Section: Characterization Of Virulence Profile Protein Secretion Andmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Some comparative studies were conducted correlating the route of experimental infection 32 or clinical manifestation in humans with the virulence degree of different isolates. 33,34 Recently, Arrillaga-Moncrieff et al 2,3 showed different degrees of virulence among S. schenckii s. str., S. brasiliensis and S. globosa species.…”
Section: Characterization Of Virulence Profile Protein Secretion Andmentioning
confidence: 99%
“…30 On the other hand, other studies showed the differences in Sporothrix virulence and the clinical presentation of the disease, geographic origin, genotype and thermotolerance. [31][32][33][34] The time of cultivation of yeast and mycelial cells of S. schenckii induces changes in cell wall composition, causing a decrease of pathogenic power. 35 Some comparative studies were conducted correlating the route of experimental infection 32 or clinical manifestation in humans with the virulence degree of different isolates.…”
Section: Characterization Of Virulence Profile Protein Secretion Andmentioning
confidence: 99%
“…The variety of clinical presentations of the disease could be due at least in part to variations in the expression of virulence factors/regulators between S. schenckii isolates. Some S. schenckii genotypes seem to be associated with particular clinical manifestations (Maia et al, 2006;Kong et al, 2006). However, the intrinsic virulence factors of this pathogen remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Kong et al (2006) reported that isolates recovered from a disseminated form of sporotrichosis were more virulent in mice than those from lymphocutaneous and fixed cutaneous sporotrichosis. Our present results indicate that all S. schenckii isolates have an intrinsic pathogenicity, but distinct dissemination patterns were observed from one isolate to another.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation